Human Discrimination Against Arcanist in Reverse 1999 Dialogues: Van Dijk 3 Dimentional Analysis - Dhiva Alfath Al Dhani; Khristianto (Faculty of Social and Political Sciences University of Bangka Belitung, 2025)
This study focuses significantly on the phenomenon of discrimination committed by humans against arcanists in the dialogue of the video game Reverse 1999. This study attempts to analyze the discrimination committed by humans against arcanists in the dialogue, explain the phenomenon of discrimination using Van Dijk's 3-dimensional theory, and identify patterns of discriminatory conversation in the dialogue of the video game. Van Dijk’s three dimensions are separated into text, social cognition, and social context. Text structure, social cognition, and social context are important parts of Van Dijk's framework. These three dimensions then analyzed using three primary structures, namely microstructure, macrostructure, and superstructure. From the text, the author identifies that the issue of discrimination appears in the elements of semantics, and rhetoric through words with discriminatory intent. In terms of social cognition, the developers place the main focus on the arcanists by portraying them as a marginalized minority group. In the social context the author concludes that social realities regarding discrimination still frequently occur in society. In fact, this problem may worsen because of domination by the dominant group.